Comparative and temporal analysis of microplastic abundance and type in urban stormwater catchments - Wan Nadiah Amalina Kadir; Bojan Tamburic; Chung Yiin Wong; Richard M. Stuetz; Andrew P. Dansie (Environmental Challenges, 2025)
Stormwater from urban areas is a well-known pathway for the transportation of plastic and microplastic pollution to the world’s oceans. However, research on microplastic abundance in urban stormwater systems is still limited and understudied compared to the marine environment. Further, temporal changes in microplastic abundance are rarely considered with the majority of studies reporting on one sampling event only. This study investigated the temporal distribution and polymer type of microplastic particles (>20 μm and <5 mm). Three ponds located in Centennial Parklands, Sydney, Australia, that receive stormwater from different urban stormwater catchments were sampled over an eight-week period. A total of 1511 particles were collected and identified according to shape and polymer type. The abundance of microplastic particles in the water samples ranged from 3.1 to 11.9 particles/L. The results showed no significant difference in plastic particle count and type among the ponds from week to week; however, they indicate that ponds within Centennial Parklands are homogeneously polluted with a variety of microplastics. The abundances of microplastics found in these urban wetlands of Sydney were higher than those reported in areas of similar urbanization. Chlorinated polyethylene was the most common polymer in all sampled ponds, at 64 % to 97.5 % of particles, while fragments being the most common microplastic particle shape observed during sampling. Temporal investigation of microplastic transport into the environment is needed to develop effective management and mitigation strategies. Long-term and ongoing microplastic monitoring in stormwater is recommended to derive an accurate estimation of its contribution to global microplastic pollution.